Bites Grill / Ezekiel Koheed H. Guntingan... [et al.] - Saiful Bahri, Siti Noor Asilah; Ahmad Mujahid, Nurfarhana; Mohd Dahali, Mohd Hanifuddin; Mohamad Ithinin, Nur Heqmah; H. Guntingan, Ezekiel Koheed (2014)
We decide to start a business a partnership, and our marketing manager decided to name our business as Bites Grill. The ideas of forming this business also came from our marketing manager and are agreed by all of us. The main idea was to prepare and serve grill based food to our community. Each of the partners is also acting as the head of the department with one person as the General Manager. We will run this business at Gaya Street because we tend to notice that these areas will serve our needs as to obtain consumers to purchase our products. We want to grab this opportunity because the idea itself will challenge the competition in Malaysian food industry and diversify the trend in our community food consumptions.